ANALISA PENGARUH BUDIDAYA SARANG BURUNG WALET TERHADAP KEPADATAN VEKTOR DI KECAMATAN PASAR KOTA JAMBI. - Guntar Marolop S (Jurnal Ilmiah Universitas Batanghari Jambi, 2010)
One of the city community efforts to improve its economy is the cultivation of bird's nest. Bird's nest can be made at the shop (the home-stores) by conditioning the shop as same as habitat for birds swallow, so the bird nest cultivation has increased,  including in the District Pasar of Jambi city.bird's nest Cultivation also come with negative impact, i.e. influence on public health. One of them is against the vector density. To find increased density vector can be analyzed through the presence of larvae in the pond water of bird nest building (container index, CI) and in places the water in the home and outside the home (house index, HI) around the location of bird's nest.The results showed that the bird nest cultivation in Jambi City Market District affect vector density; obtained CI = 7.91% and HI = 14.24%. CI and HI of this magnitude exceed the value of ≤ 5% dengue endemic area of Jambi city.Key words : Burung walet, vektor, jentik, container index, house index